2019
DOI: 10.1111/cogs.12705
|View full text |Cite
|
Sign up to set email alerts
|

Learning Words Via Reading: Contextual Diversity, Spacing, and Retrieval Effects in Adults

Abstract: We examined whether variations in contextual diversity, spacing, and retrieval practice influenced how well adults learned new words from reading experience. Eye movements were recorded as adults read novel words embedded in sentences. In the learning phase, unfamiliar words were presented either in the same sentence repeated four times (same context) or in four different sentences (diverse context). Spacing was manipulated by presenting the sentences under distributed or non‐distributed practice. After learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 65 publications
(97 reference statements)
6
37
0
Order By: Relevance
“…This means that, in the full absence of comprehension problems, diversity only had a positive impact, making the pseudowords easier to recall, recognize, and match with their meaning. Our results are in line with prior studies that show effects of diversity above and beyond those of frequency 4,20,22 . This suggests that simply manipulating contextual diversity might be enough to improve performance without increasing frequency of exposure.…”
Section: Discussionsupporting
confidence: 93%
“…This means that, in the full absence of comprehension problems, diversity only had a positive impact, making the pseudowords easier to recall, recognize, and match with their meaning. Our results are in line with prior studies that show effects of diversity above and beyond those of frequency 4,20,22 . This suggests that simply manipulating contextual diversity might be enough to improve performance without increasing frequency of exposure.…”
Section: Discussionsupporting
confidence: 93%
“…The findings reported by Bolger and colleagues (2008) are consistent with this, in that their varied contexts yielded better acquisition than presenting participants with an identical context repeatedly. These findings are also consistent with other studies that have shown that repeated exposures to novel or less familiar words helps with learning the words (Eskenazi et al, 2018;Jenkins et al, 1984;Pagán & Nation, 2019). However, when the context was inconsistent across encounters, memory performance was not nearly as strong in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, Bolger and colleagues (2008) argued that it is particularly beneficial to learn new words within a range of varied contexts, resulting in a more abstract understanding of their meanings, when compared with a single repeated context or a single definition that does not provide any of the words' nuances. Pagán and Nation (2019) provided evidence of the benefit of exposures to unfamiliar words in varied context but within an incidental acquisition paradigm, instead of explicit instruction. Eskenazi and colleagues (2018) also found that multiple exposures to novel words increased word learning, even when the words were in uninformative contexts.…”
Section: Contextual Use In Incidental Vocabulary Acquisitionmentioning
confidence: 99%
“…Overall, eye movement monitoring while reading novel words appears as particularly useful for the real-time study of orthographic learning . Most previous studies focused on the effect of the learning context on eye movements, focusing on the order-of-acquisition (Joseph et al, 2014), contextual diversity, spacing and retrieval practice (Pagan & Nation, 2019) or the diversity of semantic contexts (Joseph & Nation, 2018). Only a few studies manipulated the number of exposures and studied eye movement changes throughout exposures (Gerbier et al, 2015(Gerbier et al, , 2018Joseph & Nation, 2018;Joseph et al, 2014).…”
Section: Introductionmentioning
confidence: 99%